The GRDP Per Capita Gap between Provinces in Indonesia and Modeling with Spatial Regression - Desy Wasani; Setyorini Indah Purwanti (Department of Mathematics, Hasanuddin University, 2022)
Gross Regional Domestic Product (GRDP) is one of the key indicators to determine the economic conditions in an area within a certain period, both based on current prices and constant prices. The GRDP per capita shows the value of GRDP divided by the mid-year population. According to data from Statistic Indonesia (BPS), the distribution of GRDP is concentrated in Java. About 59 percent of Indonesia's economy in 2021 was contributed by Java. The contribution of other islands is not more than 10 percent, except for Sumatra at 21 percent. One of the government's policies to equalize the economy announced in 2019 was the relocation of the nation's capital city from DKI Jakarta to East Kalimantan. This policy has generated polemics in various circles of society regarding priorities, urgency, procedures, and risks. The economic inequality between regions in Indonesia involves various regions or provinces with different characteristics. Spatial regression is a model that accommodates spatial effects because the observation unit is a location. The aim of this study is to determine the level of economic disparities between provinces in Indonesia, resulting in the decision to relocate the nation's capital city. In addition, the aim is to determine the significance of several factors that affect GRDP per capita as a measure of regional prosperity, namely population density, number of workers, and the Human Development Index.